Neurocritical Care for the Advanced Practice Clinician (Springer International Publishing, 2018)
By utilizing a review of case-based studies and providing concise management recommendations from leaders in the field, this book provides essential knowledge for those practicing in a dynamic specialty. In the rapidly developing field of Neurocritical Care, Advanced Practice Clinicians have become an integral component of the multi-disciplinary team. This essential volume provides a frame of reference for advanced practice nurses, physician assistants, physicians, and students on a wide range of common Neuro ICU diagnoses and management strategies.